La España de los años cuarenta: contexto político, social, religioso y cultural - Montero Díaz, Julio (Studia et Documenta, 2021)
La Guerra Civil concluyó con la derrota militar de un bando, sin acuerdos. El país estaba económicamente destrozado. En muy amplia medida, la contienda supuso el triunfo de principios culturales y sociales propios de los diversos tradicionalismos anteriores a la Segunda República. Durante estos años se forja la generación que asumirá el poder a partir de los años cincuenta. El estrecho marco de libertades eliminó propiamente la lucha política. En su vertiente positiva, representó la reconstrucción de España en todos sus órdenes; en negativo, la fuerte represión y “limpieza” del bando derrotado.
Spain in the 1940s: Political, Social, Religious and Cultural Context
The Civil War concluded with the military defeat of one side, with no agreements. The country was economically devastated. To a very large extent, the conflict led to the triumph of cultural and social principles typical of the various traditionalisms that existed before the Second Republic. During those years, the generation that would take power from the 1950s onwards was forged. The narrow framework of freedom effectively eliminated political struggle. On the positive side, it represented the reconstruction of Spain in all its aspects; on the negative side, it represented the strong repression and "cleansing" of the defeated side.
Keywords: represión; jerarquía eclesiástica; falange; tradicionalistas; monárquicos; reconstrucción; universidad; práctica religiosa; España; 1940-1950; repression; church hierarchy; traditionalists; monarchists; reconstruction; university; religious practice; Spain; Emerging